Status, population trend and genetic structure of South American fur seals, Arctocephalus australis , in southwestern Atlantic waters - Crespo, Enrique Alberto (2015)
The South American fur seal (SAFS), Arctocephalus australis, was severely depleted during the 18th century. This work updates information on distribution, abundance, seasonal movements, and genetic structure along the southwestern South Atlantic. Its distribution in Argentine waters includes nineteen rookeries on the Patagonian coast, Isla de los Estados, and islets of the Beagle Channel. Censuses were carried out in rookeries from Isla Escondida to Isla de los Estados from 1996 to 2014. The largest concentrations are found in Chubut, (4,500–15,500 seals) and Isla de los Estados (4,500). Pups were recorded on Isla Escondida, Rasa, and Isla de los Estados. An increasing number of SAFS were recorded in northern Patagonia, including seals marked in Uruguay. Skin samples were taken from southern Brazil to Tierra del Fuego in order to evaluate population structure and demographic trends. Genetic results indicated no population subdivisions (Φst = −0.0292, Fst = −0.00716, P > 0.05). Bayesian skyline plots constructed for the entire data set indicated evidence of rapid population expansion discernible in Nef between the last 20,000 and 17,000 yr. Genetics results and observation data from marked fur seals support the hypothesis of ancient gene flow and a single Atlantic population. Therefore, SAFS should be managed under international and integrated conservation policies.